Calorie Restriction and Moderate-Intensity Continuous Exercise Decrease Free Fatty Acid Levels and Visceral Fat Weight on High Calorie Diet Female Mice - Ahmad Rukhani Lutfi; Lilik Herawati; Widjiati; Gadis Meinar Sari (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: This study aimed to analyze the effect of a combination of calorie restriction and moderateintensity continuous exercise on FFA levels and visceral fat weight in female mice exposed to a high-caloriediet.Material and Method: This research was randomized posttest used only control group design with femalemice as the sampl Balb/c mice (Mus musculus), 8 weeks old, 20-30 grams. It was randomly divided into fourgroups, namely C (control group), G1 (moderate-intensity continuous exercise group), G2 (calorie restrictiongroup), and G3 (combination group calorie restriction and moderate-intensity continuous exercise) wherein every group consisted six female mice. Providing a high-calorie diet using ad libitum plus D40 as muchas 3-5% of calories (0.0325 mL/gBB) for 4 weeks. The provision of a high-calorie diet was done usingthe sonde technique. Calorie restriction was done 3x/week in 4 weeks by limiting calorie intake to 50% ofstandard foods. The moderate-intensity continuous exercise was carried out by swimming for 15 minutesplus 6% gBB loading, it was done 3 times/week for 4 weeks. The measurement of cholesterol, visceral fatweight, and FFA level was done at the end of treatments.Results: The results found that the mean of cholesterol of C C (171.00±47.74 mg/dL), G1 (126.00±15.92 mg/dL), G2 (131.50±22.37 mg/dL), G3 (121.17±21.23 mg/dL) dan (p=0.032). The mean weight of visceral fatat C (0.68±0.23 grams), G1 (0.25±0.08 grams), G2 (0.28±0.06 grams), G3 (0.20±0.03 grams) and (p=0.000).The mean FFA levels were at C (1511.34±6.19 µmol/L), G1 (1419.31±53.61 µmol/L), G2 (1458.20±28.89µmol/L), G3 (1451.55±43.77 µmol/L) and (p=0.004).Conclusion: Based on the results of the study, it could be concluded that the provision of calorie restrictionand moderate-intensity continuous exercise significantly reduced cholesterol levels, visceral fat weight, FFAlevels and in female mice exposed to a high-calorie diet